منهج السنة في المحافظة على البيئة (دراسة حديثية تأصيلية) / PRESERVING THE ENVIRONMENT BASED ON SUNNAH APPROACH (MODERN AND CONTEMPORARY STUDIES) - Aisyah, Aisyah; Rasyid, Daud (Jurnal Adabiyah, 2021)
تهدف هذه الدراسة إلى تحليل تغير المناخ والأثر السلبي للأضرار البيئية. هذه الدراسة عبارة عن مراجعة للأدبيات ، كلاسيكية ومعاصرة. الطريقة المستخدمة هي طريقة نوعية ذات منهج وصفي من خلال جمع الأحاديث المتعلقة بالبيئة. وجدت نتائج الدراسة أن درجة حرارة الهواء تزداد دفئًا ، وتغير المناخ موزع بالتساوي ، وتلوث الهواء في كل مكان ، وظهور أمراض أو فيروسات مختلفة دليل على أن البيئة (الأرض) قد تضررت. يبدأ الضرر في الواقع من السلوك البشري نفسه. الظواهر الطبيعية ليست سوى تأثير الضرر البشري. الطبيعة متاحة لرفاهية الإنسان ، يسيء استخدامها عدد قليل من البشر لإشباع رغباتهم على حساب المزيد من البشر. الاستنتاج الذي تم التوصل إليه هو أن الاكتشافات العلمية الحديثة تتماشى مع محتوى الحديث النبوي ، حتى قول الرسول صلى الله عليه وسلم يسبق الاكتشافات العلمية الحديثة الكلمات المفتاحية: بيئة; حماية; السنة الشريعة الإسلامية; الاحتباس الحرارى ABSTRACT This study aims to analyze climate change and the negative impact of environmental damage. This study is a literature review, classical and contemporary. The method used is a qualitative method with a descriptive approach by collecting hadiths related to the environment. The results of the study found that the air temperature is getting warmer, climate change is evenly distributed, air pollution is everywhere, the emergence of various diseases or viruses is evidence that the environment (earth) has been damaged. The damage actually starts from human behavior itself. Natural phenomena are only the impact of human damage. Nature is available for human welfare, abused by a few humans to satisfy their desires at the expense of more humans. The conclusion obtained is that modern scientific findings are in line with the content of the Prophet’s hadith, even the Prophet’s statement precedes modern scientific findings.